Introns provide a platform for intergenic regulatory feedback of RPL22 paralogs in yeast - Abrhámová, Kateřina; Nemčko, Filip; Libus, Jiří; Převorovský, Martin; Hálová, Martina; Půta, František; Folk, Petr (PLOS ONE, 2018)
Ribosomal protein genes (RPGs) in Saccharomyces cerevisiae are a remarkable regulatory group that may serve as a model for understanding genetic redundancy in evolutionary adaptations. Most RPGs exist as pairs of highly conserved functional paralogs with divergent untranslated regions and introns. We examined the roles of introns in strains with various combinations of intron and gene deletions in RPL22, RPL2, RPL16, RPL37, RPL17, RPS0, and RPS18 paralog pairs. We found that introns inhibited the expression of their genes in the RPL22 pair, with the RPL22B intron conferring a much stronger effect. While the WT RPL22A/RPL22B mRNA ratio was 93/7, the rpl22aΔi/RPL22B and RPL22A/rpl22bΔi ratios were >99/<1 and 60/40, respectively. The intron in RPL2A stimulated the expression of its own gene, but the removal of the other introns had little effect on expression of the corresponding gene pair. Rpl22 protein abundances corresponded to changes in mRNAs. Using splicing reporters containing endogenous intron sequences, we demonstrated that these effects were due to the inhibition of splicing by Rpl22 proteins but not by their RNA-binding mutant versions. Indeed, only WT Rpl22A/Rpl22B proteins (but not the mutants) interacted in a yeast three-hybrid system with an RPL22B intronic region between bp 165 and 236. Transcriptome analysis showed that both the total level of Rpl22 and the A/B ratio were important for maintaining the WT phenotype. The data presented here support the contention that the Rpl22B protein has a paralog-specific role. The RPL22 singleton of Kluyveromyces lactis, which did not undergo whole genome duplication, also responded to Rpl22-mediated inhibition in K. lactis cells. Vice versa, the overproduction of the K. lactis protein reduced the expression of RPL22A/B in S. cerevisiae. The extraribosomal function of of the K. lactis Rpl22 suggests that the loop regulating RPL22 paralogs of S. cerevisiae evolved from autoregulation.